The Gesta Tancredi of Ralph of Caen : a History of the Normans on the First Crusade. - Bachrach, Bernard S., 1939- (Crusade texts in translation., 2007)
This is the first translation into English of Ralph of Caen's Gesta Tancredi. The text provides an important narrative of the First Crusade and its immediate aftermath, covering the period 1096-1105. The work as a whole has a striking Norman point of view and contains details found in no other source, providing a corrective to the strong northern focus of most of the other narrative sources for the First Crusade.